2003
DOI: 10.1046/j.1469-8137.2003.00846.x
|View full text |Cite
|
Sign up to set email alerts
|

Some reflections on double fertilization, from its discovery to the present

Abstract: Contents Summary  000 Introduction  000 Discovery of double fertilization  000 Seed development without double fertilization  000 A case for double fertilization in gymnosperms  000 Structural and cytological perspectives on double fertilization  000 In vitro double fertilization  000 Genetic and molecular perspectives  000 Concluding comments  000 Acknowledgements  000 References  000 Summary The fusion of one sperm with the egg cell to form the embryo and of the other sperm with the polar fusion nucleus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
77
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 192 publications
0
77
0
2
Order By: Relevance
“…Fertilization and subsequent events in angiosperms, such as embryogenesis and endosperm development, occur in the embryo sac deeply embedded in ovular tissue (Guignard 1899;Nawaschin 1898;Raghavan 2003;Russell 1992). Since investigations into the molecular mechanisms of fertilization and embryogenesis have been impeded by the difficulties in directly researching the biology of the embedded female gametophyte, zygote and early embryo, studies for these mechanisms have been conducted predominantly through analyses of Arabidopsis mutants or transformants coupled with live imaging (reviewed in Berger 2011;Denninger et al 2014;Hamamura et al 2012Hamamura et al , 2014Maruyama et al 2015).…”
mentioning
confidence: 99%
“…Fertilization and subsequent events in angiosperms, such as embryogenesis and endosperm development, occur in the embryo sac deeply embedded in ovular tissue (Guignard 1899;Nawaschin 1898;Raghavan 2003;Russell 1992). Since investigations into the molecular mechanisms of fertilization and embryogenesis have been impeded by the difficulties in directly researching the biology of the embedded female gametophyte, zygote and early embryo, studies for these mechanisms have been conducted predominantly through analyses of Arabidopsis mutants or transformants coupled with live imaging (reviewed in Berger 2011;Denninger et al 2014;Hamamura et al 2012Hamamura et al , 2014Maruyama et al 2015).…”
mentioning
confidence: 99%
“…The egg and central cells fused with each sperm cell develop into an embryo, which transmits genetic material from the parents to the next generation, and into an endosperm, which nourishes the developing embryo/seedling, respectively. [23][24][25][26] It has been indicated that polyspermy block functions in the egg cell [27][28][29][30] and the central cell 30 to promote faithful double fertilization 31 . In addition, Ca 2C -dependent egg activation occurs in plants as well as animals, [32][33][34] and it has been postulated that the increased Ca 2C level triggers the polyspermy block of fertilized egg cells via Ca…”
Section: Polyspermy and Polyspermy Blockmentioning
confidence: 99%
“…In gymnosperms, this occurs after meiosis; in angiosperms, it is after double fertilization. Although they differ in the initial events that bring about syncytial development (Raghavan, 2003), the outcome is similar: the initial cell increases in size while nuclei continue to divide in the absence of any cell wall formation. During this period, these cells can reach high ploidy levels.…”
Section: Introductionmentioning
confidence: 96%